On the definition of a contact within the Sretenskii model class - Dubovenko, Yu. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
The inverse contact problem of gravity inversion for a density interface within the Sretenskii class is posed. A discontinuity of the gravity vertical derivative, which appears on problem's right-hand side, is proved. This feature is used to reduce the problem to the alternative statement in the form of the 1st kind integral equation. By means of the residual analysis of the boundaries for the corresponding integrals, an efficient technique for the successive calculation of the density interface is developed. The problem is generalized onto the case of n boundaries, while preserving its correctness within the Sretenskii class.